Internal Risk Financing through Captive Insurance: A Special Focus on The Structure, and Trend & Developments of Five Major Captive Insurance DOMICILES - Verma, Vaibhav (2008)
ABSTRACT Captive Insurance, a technique for internal risk financing is an insurance company that only insures all or part of the risk of its parent company. (Kloman et al, 1982) It is one such area in the field of risk financing which has always remained undercover due to the complexity attached in the form of sensitivity in information disclosure and confidentiality of data. So the objective of this dissertation is to examine the captive insurance industry, with a special focus on its five major domiciles - Bermuda, Cayman Islands, Vermont, British Virgin Islands and Guernsey, their structure and their recent trends and developments. Various research and data collection techniques have been used to perform the research in the field of captive insurance industry and more precisely its five major domiciles. The dissertation begins with a literature review providing an insight of what the previous researchers have explored in the captive insurance field of risk financing. It is followed by a research methodology that has been structured so as to carry out the research in an efficient manner. Examining the overall captive market indicated that captive insurance market is governed by five of its major domiciles Bermuda, Cayman Islands, Vermont, British Virgin Islands and Guernsey, with Bermuda being the main choice of domicile. So the main focus of this dissertation is to examine the structure, and trends & developments of these five domiciles.